A systematic review of consumer perceptions of food fraud and authenticity: A European perspective. (December 2019) - Kendall, Helen; Clark, Beth; Rhymer, Caroline; Kuznesof, Sharron; Hajslova, Jana; Tomaniova, Monika; Brereton, Paul; Frewer, Lynn
Abstract: Background: Food fraud results from deliberate criminal intent to adulterate or misrepresent food, food ingredients or packaging, and is motivated by economic gain. Its occurrence has been identified across various supply chains within local, regional and global food systems, including within Europe. Incidents of food fraud may negatively impact on consumer confidence of the food industry and in regulatory mechanisms designed to prevent or mitigate food fraud. A systematic analysis of the impacts of European food fraud incidents on European consumer perceptions and attitudes is presented. Scope and approach: Three databases were searched, yielding 15 studies. Thematic analysis of the results yielded six themes "drivers of fraud", "consumer fraud concerns", "consumer perceptions and attitudes following a food fraud incident", " responsibility, accountability and blame " and " consumer behavioural response ", and " supply chain responses ", but not increased food risk perceptions. This may be an artefact of the search language (English) used, the time period of the search (20 years from 1998) and because academic interest in food fraud as a distinct topic of study has been relatively recent, in particular from a risk perception perspective. Key findings and conclusions: Understanding consumer perceptions and attitudes towards food fraud, authenticity, and trust will facilitate industry and governmental priorities about food fraud prevention strategies, mitigatory actions and communication about these with the public. However, research is needed which links the perceptions and attitudes of consumers in countries to specific incidents, and to assess the impacts of preventative and mitigatory actions in relation to consumer confidence in affected food supply chains and food supply system more generally. Highlights: Food fraud may undermine the integrity of the European food system. A systematic search revealed only 15 papers published from 2012 onwards. Reassurances around product origin is one way to gain trust. Consumer responses to several serious incidents have not been academically studied. European consumers do not usually view fraud as a risk to food safety.